Disciplinas jurídicas en revistas españolas. Un repertorio bibliográfico (1836-1935) - Liendo-Tagle, Fernando (Historia del Derecho, 2023)
Repertoire and selection of references consisting of more than 1600 individual references that were published in Spanish law journals between 1836 and 1935. The fundamental criterion for the organisation of the material was the attribution of each reference to a specific legal discipline or area of interest. The aims of this repertoire are: i) to present references that are largely unknown and/or scarcely worked in historiography; ii) to provide data to researchers when they are looking for a legal concept or institution of their interest, thus leading them to find primary sources; iii) to present references when inquiring about a specific author; iv) to provide data on how a legal book was received in its historical moment through the reviews and commentaries of the period covered; iv) to provide references on the study and teaching of a legal discipline and on legal studies in general.